Common Law, Civil Law, and Colonial Law Essays in Comparative Legal History from the Twelfth to the Twentieth Centuries - Eves, William; Hudson, John; Ivarsen, Ingrid; White, Sarah B. (Social Sciences, 2021)
This book's audience will be academics and undergraduate and postgraduate students working in the fields of legal history and comparative history, as well as History and Law more generally. The essays will also be of interest to practitioners with an interest in legal history. This title is also available as Open Access on Cambridge Core.